Whole brain irradiation with simultaneous integrated boost in treatment of oligometastatic brain disease - Kolarevic, Goran; Jaroš, Dražan; Ćazić, Dejan; Djokanović, Dejan (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Brain metastases occur in 20%–30% of all patients with systemic cancer. We aimed at investigating whether patients with oligometastatic brain disease treated with whole brain radiotherapy (WBRT) and simultaneous integrated boost of brain metastases (SIBmets) improved overall survival (clinical outcomes) compared with patients from the Radiation Therapy Oncology Group (RTOG) 9508 database, treated with WBRT and sequential stereotactic radiosurgery (SRS) boost. Methods. WBRT with SIBmets, using the RapidArc (RA) (Varian Medical Systems, Palo Alto, CA) volumetric modulated arc technique (VMAT), was delivered to 15 patients with computed tomography/magnetic resonance imaging (CT/MRI) findings of 1–3 brain metastases with a diameter less than 40 mm for the largest lesion. Radiotherapy (RT) plans consisted of WBRT, with a prescribed dose of 20 Gy in 5 fractions, with SIBmets which was also 20 Gy (gray units) in 5 fractions. Results. A group of 15 patients included 8 males and 7 females with the mean age of 56.3 years. Three patients were in the RTOG Recursive Partitioning Analysis (RPA) Class I and other 12 patients in RPA Class II. Four patients had one metastasis and 11 patients had two metastases. Calculated mean survival time (MST) was 7.49 ± 4.36 months with no statistically significant difference compared to RTOG 9508 results (MST = 6.5 months) (p = 0.197). The local control rate for 7 patients after three months was 85.7%. Conclusion. WBRT with SIBmets and WBRT + SRS are clinically equivalent treatment options for the patients with oligometastatic brain disease. In comparison to the WBRT + SRS, the treatment by WBRT + SIBmets technique reduces the treatment time and improves the patient’s treatment comfort.